(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2004)
Based on a continuous succession of ammonite and calcareous nannofossil assemblages, the main purpose of this paper is the correlation between ammonite and calcareous nannofossil zone boundaries in two expanded sections from the Basque-Cantabrian area. The ammonite assemblages show clear euroboreal features and allow the identification of Pliensbachian-Toarcian zones and subzones established for NW Europe. Due to the presence of Mediterranean taxa documented at different levels, they are also helpful to improve the biocorrelations between Boreal and Tethyan successions. The calcareous nannofossil assemblage changes provide a useful set of easily recognizable events that facilitate the recognition of all the Pliensbachian-Toarcian zones described for NW Europe and Mediterranean Province. Based on the FO Similiscutum cruciulus (Jamesoni Zone), FO of Lotharingius hauffii (Stokesi/Margaritatus Zone boundary), FO of Carinolithus superbus (Serpentinus Zone), FO of Discorhabdus striatus (Serpentinus/Bifrons Zone boundary) and FO of Retecapsa incompta (Insigne Zone), the NJ3/NJ4, NJ4/NJ5, NJ5/NJ6, NJ6/NJ7 and NJ7/NJ8 Zone boundaries have been recognized. Besides, the NJ4, the NJ5 and the NJ6 span almost the same ammonite-defined time interval in both NW Europe and Basque-Cantabrian area. With respect to the ammonite zone, the zone boundaries NJ3/NJ4 and the NJ6/NJ7 coincides with the NJT3/NJT4 and the NJT6/NJT7 proposed for Mediterranean Province. Instead, the zone boundaries NJ4/NJ5 and the NJ5/NJ6 not coincides with the NJT4/NJT5 and the NJT5/NJT6 proposed for Mediterranean Province. Furthermore, in NW Europe and Mediterranean Province the FO of Retecapsa incompta is placed in the Levesquei Zone and Meneghinii Zone, whilst in the Basque Cantabrian area it lies in the Insigne Zone.